A new Critically Endangered species of stone breaker (Phyllanthus, Phyllanthaceae) from Central Brazil, with notes on its leaf and stem anatomy - Silva, Marcos José Da; Alonso, Alexandre Antônio; Santos, Igor Soares Dos (Phytotaxa, 2022)
A new species from the state of Goiás, Brazil, Phyllanthus pterocaulis, is described and illustrated, with comments on its geographic distribution and environmental preferences, phenology, morphological relationships, and systematic position. It is morphologically allied with Phyllanthus avicularis, P. heliotropus, and P. hyssopifolioides, but differs from all of them by a set of characters related to cymules sex, presence and types of trichomes on leaves and stems, leaf consistency, numbers of sepals in flower of both sexes, integrity of stamens, capsules and seeds. Additionally, we provide images of the new species in the field, conservation status, mapped distribution, the anatomical description of its stem and leaves, and a key to differentiate it from the other similar species belonging to Phyllanthus sect. Loxopodium occurring in Brazil. The new species is one of the few in the genus that occurs in shaded environments in seasonal dry forests within the Cerrado biome.